Aktualisasi Nilai-Nilai Tasawuf dalam Buku Wasiat Renungan Masa Karya TGKH. Muhammad Zinuddin Abdul Madjid di Madrsah Aliyah Mu’alimin NW Anjani - Gani, Abdul; Fahururrozi, Fahururrozi; Thohri, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Sufism, a significant aspect of Muslim life, emphasizes spiritual development and the individual's connection with God. TGKH. Muhammad Zinuddin Abdul Madjid's book